Concomitant cholelithiasis and acute (chronic) pancreatitis after thyroidectomy: case report - S. N. Styazhkina; E. V. Korovkina; A. G. Gevorkyan; Yu. V. Moskvina (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2020)
Cholelithiasis and acute/chronic pancreatitis are some of the most common diseases in the practice of any doctor. There are numerous causes of cholelithiasis and pancreatitis (age, female gender, pregnancy, obesity, etc.), but the impact of hormones on these disorders is still poorly understood. One of the conditions for the formation of stones in the biliary tract is an increased level of fat in blood. Adrenocorticotropic hormone, somatotropic hormone, thyrotropic hormone, insulin, and thyroid hormones have lipotropic activity. In particular, deficiency of thyroxine and triiodothyronine disrupts fat metabolism in the body. There is also some evidence that reduced evacuation function of the gastrointestinal tract increases the risk of cholelithiasis, which is probably a result of hypothyroidism. Pancreas functioning is also affected by hormones. Hypothyroidism can be accompanied by a decrease in calcitonin secretion, which will eventually lead to the development of chronic pancreatitis.Objective: to analyze the studies evaluating the impact of hypothyroidism on the formation of concretions in the biliary tract and the risk of acute or chronic pancreatitis and to report a case.Materials and methods. We analyzed the impact of hypothyroidism on the incidence of cholelithiasis and acute or chronic pancreatitis and reported a case of these disorders.Results and discussion. There is evidence that patients with hypothyroidism have increased serum levels of cholesterol; hypothyroidism causes cholestasis, while in patients with cholelithiasis, concomitant thyroid disorders significantly reduce the contractility of the gall bladder. Cholelithiasis was observed in 44.6% of patients with thyroid nodules, 33.3% of patients with autoimmune thyroiditis (AIT), and 22.2% of patients with primary and postoperative hypothyroidism. In 31.9% of women with thyroid hypofunction, concretions in the bile duct developed within 1–1.5 years after hypothyroidism diagnosis. In the study evaluating cases of concomitant hypothyroidism and chronic pancreatitis, the examination of patients with primary hypothyroidism revealed signs of pancreatic dysfunction in 64.1% of patients. Pancreatic dysfunction manifests itself with various changes in exocrine and endocrine functions and aggravates with hypothyroidism progression.Conclusion. Both literature data and our clinical experience confirm that hypothyroidism of any origin leads to the development of cholelithiasis and pancreatitis; therefore, the patients require preventive measures in advance.